Listening is key, but ask the right questions. - Papanikitas, AN (BMJ Publishing Group, 2017)
Sokol tells a poignant tale,1 but the message from this tragic case is precisely the opposite of how its title is phrased. Listening is key: ask someone why they sought advice from healthcare providers, and listen to the answer. Learning sets of questions and firing them at patients risks not asking the right question and not listening to the answer, because the clinician’s entire focus is on asking and not listening.